Positive Solutions of a Singular Nonlocal Fractional Order Differential System via Schauder’s Fixed Point Theorem - Zhang, X.; Mao, C.; Wu, Yong Hong; Su, H. (Hindawi Publishing Corporation, 2014)
We establish the existence of positive solutions to a class of singular nonlocal fractional order differential system depending on two parameters. Our methods are based on Schauder’s fixed point theorem.